Student Perceptions of PAD Class Teaching Method in Mechanical Engineering Practical Training: A Survey-Based Study (Journal of Interdisciplinary Insights, 2024)
This study investigates student perceptions of the PAD (Presentation, Assimilation, Discussion) Class teaching method in mechanical engineering practical training at Weifang University of Science and Technology, Shou Guang, China. Utilizing a quantitative approach with a questionnaire distributed to 260 students across four majors—Vehicle Engineering, Computer Science and Technology, Electrical Engineering and Automation, and Robotics Engineering—the research aims to evaluate overall perceptions, compare responses among different majors, and identify key factors influencing these perceptions. The results indicate positive feedback on participation, autonomy, discussion-based learning, and overall satisfaction, with significant differences among majors. The study highlights the need for tailored implementations of the PAD methodology to maximize its effectiveness across diverse engineering disciplines.
Keywords: mechanical engineering; student perceptions; practical training; quantitative study; comparative analysis